2012
DOI: 10.1073/pnas.1119414109
|View full text |Cite
|
Sign up to set email alerts
|

The ancestral SgrS RNA discriminates horizontally acquired Salmonella mRNAs through a single G-U wobble pair

Abstract: SgrS RNA is a model for the large class of Hfq-associated small RNAs that act to posttranscriptionally regulate bacterial mRNAs. The function of SgrS is well-characterized in nonpathogenic Escherichia coli , where it was originally shown to counteract glucose-phosphate stress by acting as a repressor of the ptsG mRNA, which encodes the major glucose transporter. We have discovered additional SgrS targets in Salmonella Typhimurium, a pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 66 publications
3
70
1
Order By: Relevance
“…S3 and S4, sgrS mutant alleles regulated expression of both manXYZ and yigL similarly to wild-type SgrS. These results are consistent with observations by other groups, where mutations in sgrT translation sequences had neutral effects on regulation of SgrS targets in S. Typhimurium, i.e., yigL and sopD (which encodes a secreted virulence factor in S. Typhimurium) (10,15). In sum, these data indicate that mutations that impair sgrT translation or change the distance between sgrT and the base-pairing region have no major effect on the ability of SgrS to regulate mRNA targets via base pairing.…”
supporting
confidence: 81%
“…S3 and S4, sgrS mutant alleles regulated expression of both manXYZ and yigL similarly to wild-type SgrS. These results are consistent with observations by other groups, where mutations in sgrT translation sequences had neutral effects on regulation of SgrS targets in S. Typhimurium, i.e., yigL and sopD (which encodes a secreted virulence factor in S. Typhimurium) (10,15). In sum, these data indicate that mutations that impair sgrT translation or change the distance between sgrT and the base-pairing region have no major effect on the ability of SgrS to regulate mRNA targets via base pairing.…”
supporting
confidence: 81%
“…For example, a recent study showed that a Salmonella small noncoding RNA can discriminate mRNA regions that differ by a single nucleotide (44). The picture is more complex for ct058 and ct192.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear from recent studies that there are numerous exceptions in both animals and bacteria to the localization of sRNA-binding sites in UTRs, and sites located within coding sequences of mRNAs have been verified (3,39). Moreover, it is becoming apparent that many conserved sRNAs may regulate distinct subsets of targets, namely, those that are conserved members of the sRNA's regulon and those that are regulated in some but not all of the organisms that possess that particular sRNA (9,40,41). Our study adds yet another layer of complexity to this issue.…”
Section: Discussionmentioning
confidence: 99%